A novel in‐motion alignment method for underwater SINS using a state‐dependent Lie group filter. Issue 3 (12th August 2020) - Pei, Fujun; Xu, Hao; Jiang, Ning; Zhu, Desen
Abstract: The in‐motion alignment for the underwater strapdown inertial navigation system is still a challenging problem due to various disturbances in the underwater environment. In this paper, a novel in‐motion alignment method, based on the Lie group representation, is developed. In this method, the process model is rewritten using the Lie group of the constant attitude matrix between two inertial frames as the state. An exact linear measurement model is constructed by analyzing the effect of the sensor errors in calculating the velocity vector. Next, the state‐dependent Lie group filter is designed basing on accurate derivation expressions for the covariance matrices of state‐dependent noises. The simulation and experiment results demonstrate that the proposed method can achieve better alignment accuracy and time than the existing method. The accuracy improves by 70% with the quaternion Kalman filter.